Fetal Microsatellite in the Heme Oxygenase 1 Promoter Is Associated With Severe and Early-Onset Preeclampsia. Issue 1 (January 2018) - Kaartokallio, Tea; Utge, Siddheshwar; Klemetti, Miira M.; Paananen, Jussi; Pulkki, Kari; Romppanen, Jarkko; Tikkanen, Ilkka; Heinonen, Seppo; Kajantie, Eero; Kere, Juha; Kivinen, Katja; Pouta, Anneli; et al.
Abstract : Preeclampsia is a vascular pregnancy disorder that often involves impaired placental development. HO-1 (heme oxygenase 1, encoded by HMOX1 ) is a stress response enzyme crucial for endothelial and placental function. Long version of the guanine–thymine (GTn ) microsatellite in the HMOX1 promoter decreases HO-1 expression, and the long maternal repeat is associated with late-onset preeclampsia. Our aim was to study whether the length of fetal repeat is associated with mother's preeclampsia, whether the length of fetal and maternal repeats affect HO-1 levels in placenta and maternal serum, and whether HO-1 levels are altered in preeclampsia. We genotyped the repeat in the cord blood of 609 preeclamptic and 745 nonpreeclamptic neonates. HO-1 levels were measured in 36 placental samples, and in the first (222 cases/243 controls) and third (176 cases/53 controls) pregnancy trimester serum samples using enzyme-linked immunosorbent assay. The long fetal GTn repeat was associated with preeclampsia and its severe and early-onset subtypes. Interaction analysis suggested the maternal and fetal effects to be independent. Placental or serum HO-1 levels were not altered in preeclamptics, possibly reflecting heterogeneity of preeclampsia. Carriers of the long fetal and maternal repeats had lower placental and serum HO-1 levels, respectively, providing functional evidence for the association. We conclude that the long fetal GTn repeat may increase mother's risk for especially severe and early-onset preeclampsia. The fetal and maternal risk alleles likely predispose to different disease subtypes. Abstract : Supplemental Digital Content is available in the text.